Psychological support for people prone to social anxiety disorder during emergencies: a pilot study during the COVID-19 pandemic - Avramchuk Олександр; Nizdran Олександра; Blozva Павло (Psychosomatic Medicine and General Practice, 2023)
Background: Social restrictions during the COVID-19 pandemic, such as being forced to stay at home, observing social distancing in public places, or having to switch to remote work (study), increased difficulties with social interaction. Although quarantine measures mitigated the "harmful impact of the pandemic" through psychological distancing from the typical stressors of social interaction, for individuals prone to social anxiety disorder, they contributed to the consolidation of avoidance strategies, prevented the disconfirmation of dysfunctional beliefs and unproductive expectations. Psychosocial support programs focused on affordable and flexible interventions will help improve resourcefulness, prevent excessive distress in difficult life circumstances, and relapse of comorbid mental health disorders. The aim: To study changes in symptoms and levels of psychosocial dysfunction in individuals with social anxiety disorder as a result of completing an online psychological support program based on low-intensity CBT. Materials and methods: One hundred thirteen individuals with a social anxiety disorder and/or complaints that meet the diagnostic criteria for this disorder according to DSM-5 were enrolled in an online low-intensity intervention program based on the cognitive-behavioral model during the COVID-19 pandemic. In 6 months after completing the program, 84 people underwent a mental state assessment using the SCL-90-R scale. Also, assessed was the influence of experiential (emotional) avoidance on the severity of symptoms and their reduction. Results. According to the results of the pilot study, it was found that the proposed program of psychosocial support for people suffering from social anxiety disorder contributed to the reduction of psychosocial distress and the severity of mental symptoms in the six months after its completion. Low-intensity techniques based on CBT, offered in an online format, have demonstrated effectiveness and sustainability of effects with regular practice in everyday life. Since the program is focused on reducing avoidance strategies as a pathogenetic mechanism, these changes can be considered preventive factors. Conclusions: The presented results are preliminary and limited by several factors: in particular, adaptation to martial law conditions. Considering the positive feedback from participants, the flexibility of the proposed program, and the prognostically positive results reflected in the moderate experimental effect of exposure on comorbid symptoms and the level of severity of distress, we see the perspective of further research and the implementation of the program for practical use.